Increased global placental DNA methylation levels are associated with gestational diabetes. Issue 1 (December 2016) - Reichetzeder, C.; Dwi Putra, S.; Pfab, T.; Slowinski, T.; Neuber, C.; Kleuser, B.; Hocher, B.
Abstract Background Gestational diabetes mellitus (GDM) is associated with adverse pregnancy outcomes. It is known that GDM is associated with an altered placental function and changes in placental gene regulation. More recent studies demonstrated an involvement of epigenetic mechanisms. So far, the focus regarding placental epigenetic changes in GDM was set on gene-specific DNA methylation analyses. Studies that robustly investigated placental global DNA methylation are lacking. However, several studies showed that tissue-specific alterations in global DNA methylation are independently associated with type 2 diabetes. Thus, the aim of this study was to characterize global placental DNA methylation by robustly measuring placental DNA 5-methylcytosine (5mC) content and to examine whether differences in placental global DNA methylation are associated with GDM. Methods Global DNA methylation was quantified by the current gold standard method, LC-MS/MS. In total, 1030 placental samples were analyzed in this single-center birth cohort study. Results Mothers with GDM displayed a significantly increased global placental DNA methylation (3.22 ± 0.63 vs. 3.00 ± 0.46 %;p  = 0.013; ±SD). Bivariate logistic regression showed a highly significant positive correlation between global placental DNA methylation and the presence of GDM (p  = 0.0009). Quintile stratification according to placental DNA 5mC levels revealed that the frequency of GDM was evenly distributed in quintiles 1–4 (2.9–5.3 %), whereas the frequency in the fifth quintile was significantly higher (10.7 %;p  = 0.003). Bivariate logistic models adjusted for maternal age, BMI, ethnicity, recurrent miscarriages, and familiar diabetes predisposition clearly demonstrated an independent association between global placental DNA hypermethylation and GDM. Furthermore, an ANCOVA model considering known predictors of DNA methylation substantiated an independent association between GDM and placental DNA methylation. Conclusions This is the first study that employed a robust quantitative assessment of placental global DNA methylation in over a thousand placental samples. The study provides large scale evidence that placental global DNA hypermethylation is associated with GDM, independent of established risk factors.